Implementation of Electronic Customer Relationship Management to Increase NusaTrip Customer Loyalty - Wiratama, Esmeralda Aprillia; Saputra, Reza Wiradhika; Digdowiseiso , Kumba (CV ODIS, 2024)
E-CRM (Electronic Customer Relationship Management) is the process of maximizing sales to customers and prospecting customers by using information technology such as databases, websites, customer service, e-mail, and social media marketing (Hendriyani & Raharja, 2018). The purpose of this research is to determine the implementation of e-CRM such as websites and business procedures carried out by NusaTrip in increasing customer loyalty. Apart from that, the implementation of e-CRM in the form of e-mail, sitemap and social media marketing such as Facebook, Instagram or more personal communication using WhatsApp is also expected to help NusaTrip to establish good communication with customers to increase customer loyalty. There are four factors in supporting the success of E-CRM, namely Organization Orientation, Customer Orientation, Knowledge Orientation, and Information Technology Orientation. The e-CRM provided by NusaTrip can help customers find information about the company or make hotel room reservations or purchase plane tickets easily.